2017
DOI: 10.1093/bja/aew430
|View full text |Cite
|
Sign up to set email alerts
|

Transoesophageal echocardiographic evaluation of central venous catheter positioning using Peres’ formula or a radiological landmark-based approach: a prospective randomized single-centre study

Abstract: Clinical Trial Registry of Korea: https://cris.nih.go.kr/cris/index.jsp KCT0001937.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(55 citation statements)
references
References 31 publications
7
46
0
2
Order By: Relevance
“…The authors demonstrated that by subtracting 0.5 cm from the depth derived from EL, the CVC tip could be reliably placed near the level of the carina in children aged under 5 years old . However, placing the CVC at the carina would result in positioning it in the middle part of the SVC and would be difficult to visualize by TEE …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The authors demonstrated that by subtracting 0.5 cm from the depth derived from EL, the CVC tip could be reliably placed near the level of the carina in children aged under 5 years old . However, placing the CVC at the carina would result in positioning it in the middle part of the SVC and would be difficult to visualize by TEE …”
Section: Discussionmentioning
confidence: 99%
“…Our study illustrated that the mean (SD) distance from the carina‐to‐SVC‐RAJ was 1.25 (0.94) cm. Ahn et al found that the mean (SD) distance of the carina‐to‐SVC‐RAJ was 2.6 (1.1) cm in adults. They considered a minimal distance of the carina‐to‐SVC‐RAJ was 1.5 cm, added to distance AB and distance R to be the distance of RL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, people of the same height can have different body habitus that affect the corresponding fixed catheter depth. Many studies suggested that the optimal central line depth was significantly related to the central line curvature within the human body. In this study, a height and a body surface measurement (D) are included in the prediction equation, which is further individualized and useful for wide promotion.…”
Section: Discussionmentioning
confidence: 99%